3D Game Asset Optimization Using Quadric Error Metrics And Decimate Modifier - Arifudin, Dani; Khasanah, Nurul Afifatul; Robbani, Ayat Akras (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
3D asset optimization is a crucial challenge in game development because high-polygon models increase computational load, reduce frame rates, and negatively affect user experience in real-time rendering environments. This research addresses the problem by applying the Quadric Error Metrics (QEM) algorithm through the Decimate Modifier (Collapse Mode) in Blender as a solution for mesh simplification. Various high-polygon 3D models were simplified at different reduction levels and tested in the Unity engine to evaluate their impact on performance. The evaluation included frame rate measurement, vertex and triangle count reduction, and geometric accuracy assessment using the Hausdorff Distance method. The results show FPS improvements ranging from 9% to 41%, with vertex reduction between 8% and 33% and triangle reduction between 17% and 22%, while maintaining acceptable visual fidelity. These findings demonstrate that QEM-based optimization effectively balances visual quality and rendering performance, making it suitable for resource-constrained platforms such as mobile games and VR applications.